2021
DOI: 10.3390/ijms22052759
|View full text |Cite
|
Sign up to set email alerts
|

Increased Presence of Complement Factors and Mast Cells in Alveolar Bone and Tooth Resorption

Abstract: Periodontitis is the inflammatory destruction of the tooth-surrounding and -supporting tissue, resulting at worst in tooth loss. Another locally aggressive disease of the oral cavity is tooth resorption (TR). This is associated with the destruction of the dental mineralized tissue. However, the underlying pathomechanisms remain unknown. The complement system, as well as mast cells (MCs), are known to be involved in osteoclastogenesis and bone loss. The complement factors C3 and C5 were previously identified as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Species-specific non-targeting immunoglobulins were used as isotype controls. We have demonstrated previously that Avidin is a very good tool to stain mast cells in tissue sections in various animal models ( 24 , 25 , 44 , 45 ).…”
Section: Methodsmentioning
confidence: 99%
“…Species-specific non-targeting immunoglobulins were used as isotype controls. We have demonstrated previously that Avidin is a very good tool to stain mast cells in tissue sections in various animal models ( 24 , 25 , 44 , 45 ).…”
Section: Methodsmentioning
confidence: 99%
“…Increased local activation of complement in the periodontal tissues enhances the local inflammatory response, as well as loss of tooth attachment and ultimately bone resorption among the associated clinical manifestations ( 120 ). The formation of osteoclasts, the cells responsible for the removal of mineralized tissue, is modulated by C3a and C5a anaphylatoxins, in synergy with IL-1ß ( 121 ). Recent studies suggested that the complement system and mast cells are associated with the destructive periodontitis processes of alveolar bone and tooth resorption in cats ( 121 ).…”
Section: Examples Of Hmgb1 and Complement Dysfunctions And Crosstalk ...mentioning
confidence: 99%
“…The formation of osteoclasts, the cells responsible for the removal of mineralized tissue, is modulated by C3a and C5a anaphylatoxins, in synergy with IL-1ß ( 121 ). Recent studies suggested that the complement system and mast cells are associated with the destructive periodontitis processes of alveolar bone and tooth resorption in cats ( 121 ).…”
Section: Examples Of Hmgb1 and Complement Dysfunctions And Crosstalk ...mentioning
confidence: 99%
“…With a view toward preventing periodontitis-mediated alveolar bone loss, researchers in two groups sought to determine novel factors or mechanisms associated with the regulation of osteoclastogenesis. In the first of these, Ihn et al reported that PF-3845, a selective fatty-acid-amide-hydrolase inhibitor, reduces RANKL-mediated osteoclastogenesis—including osteoclast differentiation and resorption activity—by suppressing the phosphorylation of extracellular-signal-regulated kinase (ERK) and NF-κB inhibitor [ 9 ]; meanwhile, Luntzer et al found that complement factors C3 and C5a and mast cells, together with calcium crystals, play key roles in promoting the activation of osteoclasts and increasing alveolar bone resorption [ 10 ]. Thus, the findings of both of these studies provide novel insights that will contribute to a better understanding of the associated pathomechanisms and/or the development of novel therapeutic approaches for the treatment of periodontitis.…”
mentioning
confidence: 99%